Analisis Dampak Keterbatasan Penggunaan Laboratorium IPA terhadap Persepsi Keterampilan Proses Sains Sains Siswa di SMAN Kampar Kiri dan Kampar Kiri Hulu - Siti Umaima; Neng Sholihat; Agusminarti Agusminarti (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2026)
This study analyzes the relationship between limitations in the use of science laboratories and students’ perceptions of science process skills at SMAN 2 Kampar Kiri and SMAN 1 Kampar Kiri Hulu. Using a quantitative descriptive approach with a correlational research design, the sample consisted of 119 students, including 56 from SMAN 2 Kampar Kiri and 63 from SMAN 1 Kampar Kiri Hulu, selected through stratified random sampling. The research instruments were questionnaires on laboratory usage limitations and students’ perceptions of science process skills, covering aspects like observing, classifying, interpreting, predicting, formulating hypotheses, and communicating results. The data were analyzed with descriptive analysis and Spearman Rank correlation. The results revealed that at SMAN 2 Kampar Kiri, there was no significant relationship between laboratory usage limitations and students' perceptions of science process skills (ρ = 0.062; p > 0.05). However, at SMAN 1 Kampar Kiri Hulu, a significant negative relationship was found (ρ = -0.573; p < 0.05). These findings suggest that the extent of laboratory limitations influences students' perceptions of their science process skills, especially in schools with more limited facilities. Optimizing the management and utilization of science laboratories is essential to support the development of students’ science process skills.